1995
DOI: 10.1182/blood.v86.4.1261.bloodjournal8641261
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy evaluating escalating doses of donor leukocytes for relapse of chronic myeloid leukemia after bone marrow transplantation: separation of graft-versus-leukemia responses from graft-versus-host disease

Abstract: Infusions of large numbers (> 10(8)/kg) of donor leukocytes can induce remissions in patients with chronic myeloid leukemia (CML) who relapse after marrow transplantation. We wanted to determine if substantially lower numbers of donor leukocytes could induce remissions and, if so, whether this would reduce the 90% incidence of graft-versus-host disease (GVHD) associated with this therapy. Twenty-two patients with relapsed CML were studied: 2 in molecular relapse, 6 in cytogenetic relapse, 10 in chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
163
3

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(176 citation statements)
references
References 23 publications
10
163
3
Order By: Relevance
“…This is in accordance with our previous experience in a larger group of patients, in whom we saw very few (3/44) relapses with a median and maximal follow-up of 29 and 89 months respectively (Dazzi et al, 2000a). This supports the notion that, until we have further experience with STI571, the use of DLI in compliance with the escalating dose regimen pioneered by the Memorial Sloan±Kettering group (Mackinnon et al, 1995;Dazzi et al, 2000b) may be the best way of treating CML patients who relapse after allo-SCT, defining relapse as one will.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with our previous experience in a larger group of patients, in whom we saw very few (3/44) relapses with a median and maximal follow-up of 29 and 89 months respectively (Dazzi et al, 2000a). This supports the notion that, until we have further experience with STI571, the use of DLI in compliance with the escalating dose regimen pioneered by the Memorial Sloan±Kettering group (Mackinnon et al, 1995;Dazzi et al, 2000b) may be the best way of treating CML patients who relapse after allo-SCT, defining relapse as one will.…”
Section: Discussionsupporting
confidence: 91%
“…Based on these observations, attempts have been made to treat recurrence of leukemia after transplantation by the administration to the patient of T lymphocytes from the original stem cell donor (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Especially in chronic myeloid lexikemia (CML).…”
Section: Treatment Of Relapsed Leukemia With Donor Lymphocytesmentioning
confidence: 99%
“…In patients with relapsed CML chronic phase, 70-80% complete remissions have been reported foUowing this treatment, most of which have been sustained remissions. AJthough there has been a clear association between the occurrence of acute GVHD following this treatment, and an itnti-leukemic effect, disappearance of the leukemic cells did not always coincide with the occurrence of GVHD, suggesting that GVL and GVHD reactivity after allogeneic SCT may be separated (27,28).…”
Section: Treatment Of Relapsed Leukemia With Donor Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of cytoreduction either prior to alloSCT or as part of the preparative regimen is also controversial. Extrapolating from the chronic myelogenous leukemia experience [9,10,45,46], durable responses from DLI are more frequent in the setting of less advanced disease. It has been shown that a state of minimal residual disease can be induced with high-dose chemotherapy and autologous stem cell rescue followed safely by immune therapy with a nonmyeloablative alloSCT.…”
Section: Discussionmentioning
confidence: 99%